Climate Pulmonology: When Pulmonologists Can Mitigate Climate Change and Air Pollution - Sta Maria, Paula Teresa (Philippine Journal of Chest Diseases, 2024)
The healthcare sector is mobilized into the frontline to address climate-related disasters and diseases but at the same time produces a lot of greenhouse gases. Climate pulmonology seeks to equip pulmonologists with the basic science of climate change and air pollution, and their impact on people and planetary health. A solid background on this issue will empower lung specialists to narrate the climate story to stakeholders and move towards a sustainable future.